Production of y fingerling potatoes. A study reserach from its factors for agricultural development, Huánuco - Pasquel Loarte, Lorenzo (2019)
The fingerling potato at the regional level is considered one of the best products to be sold in the wholesale markets. Huacar district of has the greatest scope in its production but at the same time limitations so the purpose of this work research was to determine the incidence of fingerling potato production in agricultural development; the current situation of its production in Huacar was analyzed, using primary and secondary sources. A level of descriptive-explanatory study was evaluated the significant relationship through indicators and to specify the results were used the deductive, inductive, synthesis and analytical methods. The results determine that the factors of production of fingerling potatoes influence Huacar's agricultural development in 2018, with a correlation value of 0.419 being a direct and positive link. It is concluded that within Huacar, the fingerling potatoes seek to strengthen the issue of economic efficiency, 80% prefer the use of their own capital and 40% has an experience of more than 11 years; which means that the production of fingerling potatoes in quantities produced as marketed is profitable under improvements in their productive performance.